The Relationship Between Self-Concept and Aggressive Behavior in Junior High School Students: Hubungan Antara Konsep Diri Dengan Perilaku Agresif Pada Peserta Didik di Sekolah Menengah Pertama - Ananda Astriani Ramadhanti; Dwi Nastiti (Academia Open, 2021)
This research is motivated by the phenomenon of aggressive behavior in junior high school students. One of the factors that influence aggressive behavior is self-concept. This study aims to determine the relationship between self-concept and aggressive behavior in students at Private Junior High School X Tanggulangin. This research is a type of quantitative research with a correlational approach. The variables contained in this study are self-concept as the independent variable and aggressive behavior as the dependent variable. This research was conducted at the Private Junior High School X Tanggulangin with a total sample of 143 and was taken with a saturated sampling technique. Data collection techniques in this study used two Likert model psychological scales, namely the self-concept scale and the aggressive behavior scale. The hypothesis in this study is that there is a negative relationship between self-concept and aggressive behavior in students at SMP Swasta X Tanggulangin. Analysis of the data used is analysis with Pearson Product Moment correlation technique using SPSS 18 for windows program. The results of the data analysis of this study showed a correlation coefficient of -0.275 with a significance of 0.000. So there is a negative relationship between self-concept and aggressive behavior in students at Private Junior High School X Tanggulangin and the initial hypothesis proposed by the researcher is acceptable. The effective contribution of self-concept to aggressive behavior in this study was 7.5%. Keywords: Self-concept, Aggressive Behavior, Students of Private Junior High School X Tanggulangin